FRAUD PATTERNS ON NGO FUNDS ACCOUNTABILITY REPORTS - Subaida Subaida; Siti Musyarofah; Prasetyono Prasetyono (Asia Pacific Fraud Journal, 2018)
The purpose of this study is to identify and analyze the fraud patterns on NGO funds accountability reports. The methodological approach used in this study is case study by conducting interview, observation and document review. The findings of this study show that the fraud patterns on the accountability report includes 1) documentation of fictitious activities, 2) fictitious term of reference, 3) fictitious narration, 4) fictitious attendance list, 5) fictitious receipts, 6) lack of controlling, and 7) auditor is not independent.